Astronomi cal Color Image Compression Using Multilevel Block Truncation Coding –Modified Vector Quantization Technique (Journal of the College of Education for Women, 2019)
A common approach to the color image compression was started by transformthe red, green, and blue or (RGB) color model to a desire color model, then applyingcompression techniques, and finally retransform the results into RGB model In thispaper, a new color image compression method based on multilevel block truncationcoding (MBTC) and vector quantization is presented. By exploiting human visualsystem response for color, bit allocation process is implemented to distribute the bitsfor encoding in more effective away.To improve the performance efficiency of vector quantization (VQ),modifications have been implemented. To combines the simple computational andedge preservation properties of MBTC with high compression ratio and goodsubjective performance of modified VQ, a hybrid MBTC- modified VQ color imagecompression method is presented. The analysis results have indicated theperformance of the suggested method is better, where the constructed images are lessdistorted and compressed with higher factor(59:1).